ANALISIS PERBANDINGAN DU PONT SISTEM DALAM MENGUKUR KINERJA KEUANGAN PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA SEBELUM DAN SAAT PANDEMI COVID-19 PERIODE 2017- 2022 - ELFIRA CINDI NIAS AGUSTINE (Soetomo Accounting Review, 2024)
This research aims to find out whether there is a comparison of financial performance before and during the Covid-19 pandemic using the Du Pont System Method in conventional banks in 2017, 2018, 2019, 2020, 2021 and 2022. The variables used include Total Asset Trun Over , Net Profit Margin, Return On Investment, Equity Multipiler, and Return On Equity. The purposive method was used to collect samples and analyzed using Du Pont System analysis equipment. Comparative testing of financial performance uses the Paired Sample T-test, where this test is carried out using the SPSS application program. The results of this research show that Total Asset Trun Over, Net Profit Margin, Return On Investment and Return On Equity had a significant influence before and during the pandemic, while Equity Multipiler did not have a significant influence before and during the pandemic.